IMPLEMENTASI METODE PEMBELAJARAN KLASIKAL PADA PELAJARAN TAHFIDZ QURAN DI MADRASAH IBTIDAIYAH DARUL QUR’AN KABUPATEN GUNUNGKIDUL - Umi Musaropah; Muhamad Mahali Mahali; Mustolikh Khabibul Umam; Jannati Jannati; SH Rahayu (Elementeris : Jurnal Ilmiah Pendidikan Dasar Islam, 2021)
This qualitative descriptive study examines the learning of tahfidz in class III MIDQ students using the classical method. Research data in this Full Day school study were collected by observation and interviews and documentation. A school that combines the pesantren education curriculum with the conventional educational curriculum. Based on the findings data, it is concluded that the application of the classical model in class III MIDQ is unique because it combines several interrelated methods, namely murojaah ma'a jama'ah, simaan Al-Qur'an, making groups or groups and imitating. This model has adjusted the conditions of the school, teachers and the age of development so that it has an impact on learning tahfidz Quran. In this classical model, the teacher as a facilitator, motivation must be grown consistently during the learning of tahfidz and murojaah. Students or students are advised to use the best possible time in learning by repeating murojaah at every opportunity.